THE STRATEGY OF AL UMANAA MODERN ISLAMIC BOARDING SCHOOL IN IMPLEMENTING LITERACY CULTURE - Supriatnoko; Hastuti Redyanita (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to obtain facts and evidence against the strategy applied by Al Umanaa Modern Islamic Boarding School Sukabumi for its assignment as a Pioneer for the School Literacy Movement. This study uses a qualitative descriptive approach and uses methods of survey, observation, and interview in collecting data with recording and note-taking techniques. The data were analyzed using agih and direct element division techniques to describe the strategy developed and implemented in Al Umanaa. The result showed that the strategies applied by Al Umanaa were: (1) providing local content literacy subjects; (2) aligning language subjects (Indonesian, English, Arabic) and literacy subjects into speaking and writing practices;(3) continuing the silent and aloud reading program on an ongoing basis under the guidance of the teachers; (4) writing the reading results in to a literacy work or presenting the reading results; (5) allocate budget per semester for book expenditure, receive book grants; and (6) improving the function of the library as a place to read, while those that are not yet available are literacy culture guidebooks and literacy shops in open areas, (7)empowering all potential human resources to realize the vision, mission, and goals to be achieved.